2019
DOI: 10.1021/acssuschemeng.9b03995
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Boride Nanostructured Thin Films with High Performance and Stability for Alkaline Water Oxidation

Abstract: Nanocrystalline cobalt boride (Co-B) thin films prepared by pulsed laser deposition were used as an anode catalyst to study the water oxidation reaction in alkaline medium. Elemental depth profiling revealed the bulk of the film to be metallic, which helps in improving conduction of charges, while the surface of the film was rich in CoOOH-type species to facilitate the oxygen evolution reaction (OER). Comparison of OER performance with boron-free samples suggests that inclusion of B helps in improving the OER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…However, the OER current was suppressed considerably (Figure d), suggesting that the edges of NiO 6 octahedra are the dominant active sites in NiB i thin films (schematically represented in Figure e). Formation of similar CoOOH and FeOOH species on the surface of Co and Fe based borides, respectively, after OER tests were reported by many authors as responsible for enhancing the OER performance.…”
Section: Origin Of Electrochemical Activity In Metal Boridessupporting
confidence: 67%
See 1 more Smart Citation
“…However, the OER current was suppressed considerably (Figure d), suggesting that the edges of NiO 6 octahedra are the dominant active sites in NiB i thin films (schematically represented in Figure e). Formation of similar CoOOH and FeOOH species on the surface of Co and Fe based borides, respectively, after OER tests were reported by many authors as responsible for enhancing the OER performance.…”
Section: Origin Of Electrochemical Activity In Metal Boridessupporting
confidence: 67%
“…The review also emphasized that metal oxide/hydroxide species act as the active center, while boron facilitates OER by modulating the interaction energies of the reaction intermediates. In our recent report on amorphous/nanocrystalline Co–B films, we proposed that boron helps in preventing complete oxidation of Co (by donating electrons) to form stable oxides, thereby facilitating formation of intermediate oxide/hydroxide species more easily, as compared to Co oxides. Looking at all these theories, it can be said with certainty that boron does not act as the active site for OER but does play a crucial role in formation of the reaction intermediates.…”
Section: Origin Of Electrochemical Activity In Metal Boridesmentioning
confidence: 99%
“…This implies that the role of boron is to assist in formation of Co 3+ states on the surface of the film. It has been reported that in case of Co-B films, B acts as the sacrificial element by donating electrons to Co, thereby protecting it from forming stable oxides [56]. In the present case, boron plays a similar role of preventing complete oxidation of Co thus permitting it in forming Co 3+ species on the surface.…”
Section: Resultsmentioning
confidence: 57%
“…In addition, the derived borides (amorphous CoB species) have been deemed to not only enlarge the active surfaces, but also protect metal atoms from being oxidized by virtue of its electron transport effect. [ 17 ] Meanwhile, the electron transfer of boron delivers enriched d population for metal sites and regulates local disorder to meet high electrochemical stability and activity. [ 18 ] Importantly, the compensation of the coordination number by doping heteroatoms with different electronegativity and atomic radius effectively stabilizes oxygen vacancies.…”
Section: Figurementioning
confidence: 99%
“…Finally, it could be verified that the Co‐MOF‐3h displayed superior electrocatalytic performance, in comparison with the pristine Co‐MOF and some Co‐based electrocatalysts (Table S1, Supporting Information). This improvement in the performance could be explained as follows: i) defective CoO bonds led to disordered coordination environment and redistributed electronic configuration around active metals, which opened more channels for OH − to react on active sites and promoted the absorption of water; ii) electrons in the defect states were easier to excite, which enhanced the conductivity and the charge mobility of pristine MOF; [ 36 ] iii) owing to the introduced B atoms, the hybridization of B 2p and Co 3d orbitals moved the Fermi level, while the chemical interaction contributed to lattice strain, lessen the energy barrier to form OOH* intermediate in OER; [ 37 ] iv) amorphous CoB species enlarged the active surface area and prevented the Co atoms from being oxidized, improving the stability of catalyst; [ 17 ] v) the introduction of boron element could reduce or compensate the negative effects from excessive defects and stabilize oxygen vacancies to improve the electrochemical activity synergistically. Hence, with regard to the pristine MOF with completed coordination, focusing on the destruction of coordination environment to arise defect‐induced disordered coordination was an appropriate principle and an efficient strategy for design electrocatalysts.…”
Section: Figurementioning
confidence: 99%